Pengaruh ukuran atau skala perseroan, pergantian auditor dan sistem pengendalian intern terhadap audit delay pada perseroan yang tercatat di Bursa Efek Indonesia - Sutono, Sutono; Sulistiyo, Heru; Ardi , Bagus Kusuma (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
During the COVID-19 PANDEMIC, culinary digital delivery-based services became the basis of Cloud Kitchen. In line with the growth of technology in all elements and the ease of using smartphones, several things have gone digital. This study aims to determine the effect of electronic word of mouth on purchase intention, which is influenced by brand attitude on travelokaeats' Instagram social media accounts. This research will employ quantitative causality and descriptive methodologies. Samples were taken using the convenience sampling technique so that a sample of 400 respondents could be obtained. Data collection was carried out by distributing questionnaires to people who had used or used Travelokaeats and also to Travelokaeats' Instagram followers. The analysis technique used is SEM, or structural equation modeling, and the analysis is carried out using software in the form of SmartPLS 4. Based on research discussions, it shows that Electronic Word of Mouth (E-WOM) has a positive influence on brand attitude on Travelokaets on Instagram, E-WOM has a positive influence on purchase intention on Travelokaets on Instagram, brand attitude has a positive influence on purchase intention on Travelokaets on Instagram, and E-WOM has a positive influence on purchase intention intervened by brand attitude on Travelokaets on Instagram. It is suggested that the Travelokaeats company improve the quality of its promotions on Instagram by providing discounts and promos to Travelokaeats users.